(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In AOM, the presence of an infected effusion in the middle ear cleft occurs in conjunction with the rapid onset of one or more local or systemic signs and symptoms of acute infection. There is an advantage in grading the severity of AOM, since treatment guidelines should be graded according to the severity of theillness. Patients and methods The present study is conducted in the ENT clinics in Razkari teaching hospital in Erbil city. The hospital is located in the center of city and it delivers services to many areas in Erbil city. This hospital which has (400) beds , receive cases either directly from their causality unit or referred cases from primary health care units (PHCS) which are distributed throughout Erbil city, the ENT clinics running by the ENT specialists with assistances of seiner house officers and deliver services to about 150 patients daily. Results One hundred children with otitis media had been included in the study in addition to 100 children with no otitis media (controls). The mean age + SD of the whole sample was 3.1 + 1.7 years, ranging from 0.3 to 6 years. The median was 3 years. The mean age + SD of the controls (3.7 + 1.6 years) was significantly (p < 0.001) higher than the mean age + SD of the cases (2.5 + 1.6 years). Discussion: In this case control study, the maximum frequency of AOM was observed in the age group 1-2 years (29%), age group 2-3 year constitute (35%), the lowest frequency was at the age group 4-5 years (21%). Moreover children up to 24 months formed (44%) of all attacks of AOM among the study population. Conclusions The highest frequency of acute otitis media occurred in the age group 1-2 years, slightly more frequent AOM attack occurred inmales.The main Clinical presentation among the cases were fever, otalgia, otorrhea, irritability ,loss of appetite , vomiting , diminished hearing and few patients presented with tinnitus andvertigo.